2012
DOI: 10.4236/jdm.2012.21022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between the effect of <i>Momordica charantia</i> (wild and hybrid variety) on hypoglycemic and hypolipidemic activity of alloxan induced type 2 diabetic long-evans rats

Abstract: This study was undertaken to evaluate the hypoglycemic and hypolipidemic effect of <i>Momordica charantia</i> (wild and hybrid variety) powder on alloxan induced type 2 diabetic male Long-Evans rats. Oral feeding of the <i>M. charantia</i> powder slightly decreased serum total cholesterol, triglyceride levels and LDL-cholesterol compared with wild, hybrid and standard drug. <i>M. charantia</i> wild variety showed more significant (p < 0.05, 0.01, 0.001) effect on blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…These results also suggest that AEMC increases the renewal and number of β cells in the pancreas as compared to untreated diabetic rats or may permit the recovery of STZ destroyed β cells and stimulates pancreatic insulin secretion [ 40 ]. In support with the present study the elevation of insulin levels was also observed with the administration of AEMC by other authors [ 36 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…These results also suggest that AEMC increases the renewal and number of β cells in the pancreas as compared to untreated diabetic rats or may permit the recovery of STZ destroyed β cells and stimulates pancreatic insulin secretion [ 40 ]. In support with the present study the elevation of insulin levels was also observed with the administration of AEMC by other authors [ 36 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…Le reste des plantes n'a pas encore fait l'objet d'une publication en rapport avec le diabète. Parmi les plantes qui ont le plus fait l'objet d’étude scientifique en rapport avec le diabète figure en tête de liste Momordica charantia qui a fait l'objet d'environ une dizaine de publications dans le domaine [ 4 , 15 , 22 – 27 ]. Cette plantes est suivie de quatre autres plantes qui ont fait l'objet d'au moins cinq publications dans le domaine.…”
Section: Discussionunclassified
“…In case the overall proportion test shows evidence against equality of likelihoods of the six models, it is of interest to identify which model(s) may have a relatively higher chance of to be selected by an IC. This is done by multiple comparisons tests [74], which performs pairwise comparisons of all 6 C 2 = 15 pairs of proportions. For example, the hypothesis that model 1 and model 2 are equally likely to attain a minimum value of a given IC (i.e., equally likely to be selected) is denoted as follows.…”
Section: Pairwise Test: Multiple Comparisonsmentioning
confidence: 99%